1992
DOI: 10.1111/j.1699-0463.1992.tb04032.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of post‐embedding immunoelectron microscopy in the diagnosis of glomerular diseases

Abstract: Fifty renal biopsies were studied by immunoelectron microscopy after embedding in a partly hydrophilic polyacrylic resin (LR White). Immunofluorescence studies were carried out on frozen sections of parallel tissue samples. Polyacrylic embedding gave good preservation of the renal ultrastructure and precise localization of immunoglobulin and C3c antibodies within glomerular electron‐dense deposits. Non‐specific staining of plasma proteins within vascular lumina could easily be detected. There was good correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
3
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
4
3
0
Order By: Relevance
“…The present study has confirmed recent observations by Herrera (9) and Skjorten et al (19) that postembedding with a partly hydrophilic acrylic polymer at 54°C gives reproducible immune reactions with antibodies to serum proteins and acceptable ultrastructural morphology of the tissue. The advantage of this method is a better preservation of epitopes which would be destroyed by other techniques.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study has confirmed recent observations by Herrera (9) and Skjorten et al (19) that postembedding with a partly hydrophilic acrylic polymer at 54°C gives reproducible immune reactions with antibodies to serum proteins and acceptable ultrastructural morphology of the tissue. The advantage of this method is a better preservation of epitopes which would be destroyed by other techniques.…”
Section: Discussionsupporting
confidence: 92%
“…Six animals were killed in pairs after survival periods of 1 h, 6 h and 12 h, and blocks from the lesions were prepared for postembedding immunoelectron microscopy (9,19). These blocks were not postfixed in osmium tetroxide.…”
mentioning
confidence: 99%
“…This illustrates that IEM has higher sensitivity than IF in the sense that IEM is better suited for detecting small amounts of IgA deposits. This observation fits well with previous results on LR-white sections and highaccelerator epoxy sections [3,4].…”
Section: Diagnostic Powersupporting
confidence: 93%
“…However, IF microscopy has lower morphological resolution than ordinary light microscopy, and sometimes it is difficult to determine the position of the immune complex deposits within the glomeruli. Small immune complex deposits may also have low detectability by IF [3,4]. To overcome these problems, and to combine the ultrastructural preservation with immunolabeling of the immune complex deposits, some researchers have used an acrylic resin (LR-White) for embedding the renal biopsies for immunoelectron microscopy [4,5,6].…”
mentioning
confidence: 99%
“…This illustrates that IEM has higher sensitivity than IF, in the sense that IEM is better suited for detecting small amounts of antigen. The observation that IEM is more sensitive for labeling IgA is substantial, since the presence of minor amounts of mesangial IgA may in some cases be the only finding establishing a diagnosis of IgA nephritis, and it fits well with previous results on LR-White sections (14). Indirect immunolabeling (IEM) may give more intense labeling than a direct procedure (IF).…”
Section: Iem As Diagnostic Toolsupporting
confidence: 86%